Towards Dynamic Message Passing Protocols for Stencil-Based Communication Patterns - Suresh, Kaushik Kandadi; Ramesh, Bharath; Kuncham, Goutham Kalikrishna Reddy; Subramoni, Hari; Panda, Dhabaleswar K. DK (Proceedings / IEEE International Conference on Cluster Computing, 2025)
Halo-exchange communication patterns occur in many stencil-based HPC applications such as MiniAMR, MiniGhost, and MILC. In this pattern, each process performs a mix of inter-node and intra-node transfers. Depending on the input and processor grid size, the amount of time spent in inter-node or intra-node could dominate the total communication time. Therefore, in this work, we propose a dynamic protocol for intranode and inter-node transfers that optimizes the communication time. With the proposed designs, we show up to 48% improvements over state-of-the-art libraries in 3D stencil communication benchmarks and 28% in the MiniAMR application at a scale of 2304 processes.